2017
DOI: 10.1109/tcomm.2017.2666791
|View full text |Cite
|
Sign up to set email alerts
|

Downlink Transmission of Short Packets: Framing and Control Information Revisited

Abstract: Abstract-Cellular wireless systems rely on frame-based transmissions. The frame design is conventionally based on heuristics, consisting of a frame header and a data part. The frame header contains control information that provides pointers to the messages within the data part. In this paper, we revisit the principles of frame design and show the impact of the new design in scenarios that feature short data packets which are central to various 5G and Internet of Things applications. We treat framing for downli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…This results in a lower required bandwidth, as the figure shows. 4 The trick with increasing the blocklength in order to attain a more efficient transmission, given the reliability and the latency constraints, can also be used in a scenario in which a Base Station (BS) broadcasts to multiple terminals, as in [18]. Namely, given the total number of channel uses for broadcast, the BS can concatenate all packets intended for different users and use the resulting large packet as a input to the encoder.…”
Section: Urllc Packet Structurementioning
confidence: 99%
See 1 more Smart Citation
“…This results in a lower required bandwidth, as the figure shows. 4 The trick with increasing the blocklength in order to attain a more efficient transmission, given the reliability and the latency constraints, can also be used in a scenario in which a Base Station (BS) broadcasts to multiple terminals, as in [18]. Namely, given the total number of channel uses for broadcast, the BS can concatenate all packets intended for different users and use the resulting large packet as a input to the encoder.…”
Section: Urllc Packet Structurementioning
confidence: 99%
“…Intuitively, this offers the highest reliability, but the price is that each node needs to spend energy to decode data that it does not need, as it decodes the whole packet before seeing if there is any data intended for that node and, if yes, extract it. The tradeoff between the reliability and energy expenditure is analyzed in [18]. This technique has been termed concatenateand-code in [19], which has extended the work towards crosslayer scheduling.…”
Section: Urllc Packet Structurementioning
confidence: 99%
“…This new capacity formula explicitly characterizes the relationship between transmission rate, code blocklength and decoding reliability, thus particularly suitable for evaluating the performance of URLLC systems. The capacity of FBC has been successfully applied to the study of wireless communications with strict latency constraints, as in [6][7][8][9][10][11]. For example, reference [6] considered the energy-efficient packet scheduling problem and showed that the classical Shannon capacity may significantly underestimate the energy under FBC.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the two approaches can be considered the extremes of a trade-off between frame duration and power consumption at the devices. In this context, finite blocklength information theory can help in finding the optimal operating point on this trade-off curve, a problem addressed in greater detail in [7].…”
Section: Framing and Packetizationmentioning
confidence: 99%